Establishing an Antiracist Foundation in School Counselor Preparation: A Self Study - Caroline Lopez-Perry; Jacob Olsen; Fedelia Suleiman; Julaina Juarez (Teaching and Supervision in Counseling, 2024)
This article will discuss the findings from a collaborative self-study involving two school counseling faculty, one graduate student, and an alumna of the school counseling program who is now a first-year school counselor. Given the dearth of research exploring EducatorCounselor identity development, the researchers sought to understand how faculty prepare pre-service school counselors to engage in antiracist practices through institutional and andragogical practices and how students experience these practices in developing their EducatorCounselor identity. The findings will provide a framework for antiracist foundations in school counselor preparation and illustrate the practices needed for school counselor educators to actualize antiracist work.
Keywords: antiracist school counseling; self-study; EducatorCounselor identity